Proceedings of the Twenty-Ninth Annual ACM-SIAM Symposium on Discrete Algorithms 2018
DOI: 10.1137/1.9781611975031.157
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Graph Parameters from Random Order Streams

Abstract: We develop a new algorithmic technique that allows to transfer some constant time approximation algorithms for general graphs into random order streaming algorithms. We illustrate our technique by proving that in random order streams with probability at least 2/3,• the number of connected components of G can be approximated up to an additive error of εn using (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The latter consider worst case edge arrivals, but operate under a bounded arboricity assumption on the input graph. Very recently constant space algorithms for approximating some graph parameters (such as number of connected components and weight of the minimum spanning tree) from random order streams were obtained in [PS18] (see also [MMPS17]).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter consider worst case edge arrivals, but operate under a bounded arboricity assumption on the input graph. Very recently constant space algorithms for approximating some graph parameters (such as number of connected components and weight of the minimum spanning tree) from random order streams were obtained in [PS18] (see also [MMPS17]).…”
Section: Related Workmentioning
confidence: 99%
“…It has recently been shown that randomly ordered streams allow for surprisingly space efficient estimation of graph parameters by nontrivial memory vs sample complexity tradeoffs (see, e.g. [KKS14,MMPS17,PS18] for approximating matching size and other graph properties such as number of connected components, weight of MST and independent set size). Memory vs sample complexity tradeoffs for learning problems have also recently received a lot of attention in literature [Raz16,Raz17,KRT17,GRT18,BGY18].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, these problems have been studied extensively in the query complexity model and for sublinear-time algorithms. However, starting from the pioneering work of [55], these problems have been receiving increasing attention in the streaming literature as well [37,55,77,81]. In particular, [55] gave single-pass streaming algorithms for these problems with O(n 1−poly(ε) ) space (for bipartiteness testing, the input graph is assumed to be planar).…”
Section: Property Testing Of Connectivity Bipartiteness and Cycle-fre...mentioning
confidence: 99%
“…• Streaming Property Testing: Solving property testing problems in the streaming setting (as opposed to the more familiar query algorithms) has been receiving increasing attention lately [37,55,77,81] starting from the pioneering work of [55]. On this front, BHH has been used to prove n 1−O(ε) -space lower bounds for ε-property testing of connectivity, cycle-freeness, and bipartiteness [55].…”
Section: B3 Streaming Lower Boundsmentioning
confidence: 99%
“…A closely related model of property testing is the one where the graph arrives as a random order stream and the property testing algorithm is required to use sublinear space. Although this appears to be a less powerful model because the algorithm no longer has the ability to execute whatever queries it wants, interestingly, Peng and Sohler [PS18] show that sublinear property testing algorithms give rise to sublinear space algorithms for random order streams.…”
Section: Related Workmentioning
confidence: 99%